Teaching Vocabulary Using Semantic Mapping Technique - Arif Styo Nugroho; Ira Arini (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2021)
The aim of this research is to find out the effectiveness of Semantic Mapping technique in teaching vocabulary. Therefore, the hypothesis in this research is the student who are taught by Semantic Mapping technique achieve better than before. The design used in this research is the Pre-Experiment Design. It also has several forms such as a One-Shot Case Research, One-Group Pretest-Posttest Design, One-Group Pretest and Posttest Design also Intact-Group Comparison. One-group pretest and posttest for this research, it means there will be a pretest before giving treatment to the sample and posttest after ending the treatment. In collecting data, Pre-test and Post-test are employed. The tests are multiple choices and complete the sentences. It consists of twenty questions. The right answer will be get 1 point and for the wrong answer is zero (0). The result of this research in pretest that the highest score was 16, the lower score was 9, the median was 13,00, the mode was 14 mean was 12,90, standard deviation was 1,863, range was 7 and total score of pre-test is 387. The posttest was the highest score was 20, the lower score was 14, the median was 17,00, the mode was 16 mean was 17,07, standard deviation was 1,388, range was 6 and total score of post-test is 512. The conclusion is drawn by analyzing the average scores of pretest and posttest by using t-test formula; Sig value is 0,000 < 0,05 it means that alternative hypothesis (HA) is accepted.